Investigations into the swelling pressure of wood as a function of the anatomical direction - Mario Zauer; Juliane Porath; Robert Krüger; André Wagenführ (Physics Open)
The swelling pressure as a function of the anatomical cutting direction of European beech [Fagus sylvatica L.] and Norway spruce [Picea abies (L.) Karst.] was determined at 20 °C between 25 and 85 % relative humidity (RH). The RH was increased in steps of 20 %. The uniaxial tests were carried out on test specimens with a small cross-section. As a result, it was found that beech produces almost twice as high swelling pressures as spruce during impeded swelling. The maximum swelling pressures are reached more quickly with spruce. For both types of wood, significantly higher swelling pressures were measured in the respective tangential cutting direction than in the radial cutting direction.